You need to solve the second order homogeneous differential equation, hence, you need to write the characteristic equation, such that:

`(d^2y)/(dx^2) = k^2`

`(dy)/(dx) = k`

`k^2 - k - 12 = 0`

You need to use the quadratic formula, such that:

`k_(1,2) = (1+-sqrt(1 + 48))/2 => k_(1,2) =...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to solve the second order homogeneous differential equation, hence, you need to write the characteristic equation, such that:

`(d^2y)/(dx^2) = k^2`

`(dy)/(dx) = k`

`k^2 - k - 12 = 0`

You need to use the quadratic formula, such that:

`k_(1,2) = (1+-sqrt(1 + 48))/2 => k_(1,2) = (1+-sqrt49)/2`

`k_1 = 4; k_22 = -3`

Since the solutions to characteristic equation are real and different yields the general solution to the differential equation, such that:

`y = c_1*e^(k_1x) + c_2*e^(k_2x)`

`y = c_1*e^(4x) + c_2*e^(-3x)`

**Hence, evaluating the general solution to the given differential equation, yields **`y = c_1*e^(4x) + c_2*e^(-3x).`